War against the idols: the reformation of worship from Erasmus to Calvin - Eire, Carlos M. N. (Cambridge University Press, 1986)
In the second decade of the sixteenth century medieval piety suddenly began to be attacked in some places as 'idolatry', or false religion. Wherever these ideas became accepted, churches were sacked, images smashed and burned, relics destroyed, and the Catholic Mass abolished. This study calls attention to the centrality of the idolatry issue for the Reformation. It traces the development of Protestant iconoclastic theology and practice, provides a survey and synthesis of its unfolding from Erasmus through Calvin, and lays a foundation for understanding the Reformed ideology that stood in conflict with Catholicism and Lutheranism. Professor Eire's main thesis is that the argument against 'idolatry' was central to Reformed Protestantism, both in its theological aspect and in its political ramifications, and that it reached its fullest and most enduring expression in Calvinism.